2012
DOI: 10.18388/abp.2012_2149
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of cassia seed ethanol extract against carbon tetrachloride-induced liver injury in mice.

Abstract: Oxidative stress has been recognized as a critical pathogenetic mechanism for the initiation and the progression of hepatic injury in a variety of liver disorders. Antioxidants, including many natural compounds or extracts, have been used to cope with liver disorders. The present study was designed to investigate the hepatoprotective effects of cassia seed ethanol extract (CSE) in carbon tetrachloride (CCl(4))-induced liver injury in mice. The animals were pre-treated with different doses of CSE (0.5, 1.0, 2.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Glutathione is the predominant thiol with low molecular weight in animal cells. It effectively scavenges free radicals and ROS and significantly affects the antioxidant defense system [Xie et al 2012]. In the current study, GSH levels in serum and testes homogenates significantly decreased after H 2 O 2 administration.…”
Section: Discussionsupporting
confidence: 48%
“…Glutathione is the predominant thiol with low molecular weight in animal cells. It effectively scavenges free radicals and ROS and significantly affects the antioxidant defense system [Xie et al 2012]. In the current study, GSH levels in serum and testes homogenates significantly decreased after H 2 O 2 administration.…”
Section: Discussionsupporting
confidence: 48%
“…Moreover, anthraquinones are predominantly reported in and isolated from the seeds of C. obtusifolia (Zhang, Wang, Liu, & Tu, ). In previous studies, anthraquinones compounds, which are widely distributed in plants, were considered to play an important role as dietary antioxidants for the prevention of oxidative liver damage (Jung et al, ; Wong et al, ; Xie et al, ; Yoon & Kim, ). Therefore, we hypothesized that the seeds of C. obtusifolia and its components would be useful in the prevention of liver injuries induced by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Seo, Song, Kim, and Jang () reported the hepatoprotective effects of Cassia seed ethanol extract and its components toralactone glycoside in t ‐BHP‐induced cells death in HepG2 cells. Xie, Guo, and Zhou () reported the protective effects of Cassia seed ethanol extract against carbon tetrachloride (CCl 4 )‐induced liver injury in mice. Wong, Wong, Seligmann, and Wagner () reported the hepatoprotective effects of Cassia seed methanol extract in primary cultured hepatocytes against CCl 4 and galactosamine toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The seed displays extensive pharmacological actions, for example, modern pharmacological research has reported that the cassia seed possesses antibacterial activity (10,11). Beyond the purgative action of the cassia seed, it has also been reported to decrease blood pressure and alleviate hyperlipidemia (12), protect the liver (13), improve immunity (14) and display anti-inflammatory (15) and neuroprotective effects in models of Parkinson's disease (16,17). The cassia seed is commonly used in the treatment of hypertension, fatty liver and constipation (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the purgative action of the cassia seed, it has also been reported to decrease blood pressure and alleviate hyperlipidemia (12), protect the liver (13), improve immunity (14) and display anti-inflammatory (15) and neuroprotective effects in models of Parkinson's disease (16,17). The cassia seed is commonly used in the treatment of hypertension, fatty liver and constipation (12,13). At present, research into the pharmacodynamic properties of the cassia seed has primarily focused on the anthraquinone compounds of the seed, which are related to its effect on diarrhea (18,19).…”
Section: Introductionmentioning
confidence: 99%